2016
DOI: 10.1007/s10802-016-0171-7
|View full text |Cite
|
Sign up to set email alerts
|

Reading Comprehension in Boys with ADHD: The Mediating Roles of Working Memory and Orthographic Conversion

Abstract: Reading comprehension difficulties in children with ADHD are well established; however, limited information exists concerning the cognitive mechanisms that contribute to these difficulties and the extent to which they interact with one another. The current study examines two broad cognitive processes known to be involved in children's reading comprehension abilities-(a) working memory (i.e., central executive processes [CE], phonological short-term memory [PH STM], and visuospatial short-term memory [VS STM]) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 77 publications
4
41
0
2
Order By: Relevance
“…For example, working memory deficits show strong continuity with ADHD inattentive, hyperactive, and impulsive symptoms measured objectively (Kofler et al., ; Raiker et al., ; Rapport et al., ) and by parent/teacher report (Kofler et al., ). This study's working memory tests also show strong convergence with ecologically valid, ADHD‐related impairments in peer functioning (Kofler et al., ), reading comprehension (Friedman et al., ), parent–child relationship quality, academic success/productivity (Kofler et al., ), and organizational skills (current study). That these brief, laboratory‐based tasks with minimal face valid social, academic, or organizational demands show this robust continuity is fascinating, and speaks to the strong association between children's working memory and how successfully they navigate their social and academic worlds.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…For example, working memory deficits show strong continuity with ADHD inattentive, hyperactive, and impulsive symptoms measured objectively (Kofler et al., ; Raiker et al., ; Rapport et al., ) and by parent/teacher report (Kofler et al., ). This study's working memory tests also show strong convergence with ecologically valid, ADHD‐related impairments in peer functioning (Kofler et al., ), reading comprehension (Friedman et al., ), parent–child relationship quality, academic success/productivity (Kofler et al., ), and organizational skills (current study). That these brief, laboratory‐based tasks with minimal face valid social, academic, or organizational demands show this robust continuity is fascinating, and speaks to the strong association between children's working memory and how successfully they navigate their social and academic worlds.…”
Section: Discussionsupporting
confidence: 64%
“…Converging evidence also links ADHD‐related working memory impairments with ecologically valid, functional outcomes including peer (Bunford, Evans, & Langberg, ; Tseng & Gau, ) and parent–child relational problems (Kofler et al., ). In addition, working memory strongly predicts math (Swanson & Kim, ) and ADHD‐related reading deficits (Friedman, Rapport, Raiker, Orban, & Eckrich, ).…”
Section: Introductionmentioning
confidence: 99%
“…(20) To examine the spontaneous, immediate activation and/or suppression of forward-predictive inferences, backward-explanatory inferences, and inference-evoking textual information, as they occur online during reading comprehension by adolescents Rapid naming in Brazilian students with Dyslexia and Attention Deficit Hyperactivity Disorder 2016 Journal Frontiers in Psychology Brazil Alves, Siqueira, Ferreira, Alves, Bicalho, Celeste (17) To assess the rapid automatized naming (RAN) performance in children with reading disorder and attention deficit hyperactivity disorder (ADHD) compared with their normal peers. Reading comprehension in boys with ADHD: the mediating roles of working memory and orthographic conversion 2016 Journal of Abnormal Child Psychology USA Friedman, Rapport, Raiker, Orban, Eckrich (16) To examine two cognitive aspects of processes involved in reading and comprehension abilities -(a) working memory and orthographic conversion (phonological text conversion) -in order to elucidate their interactive contribution to reading comprehension differences. Naming speed of adolescents and young adults with Attention Deficit Hyperactivity Disorder: differences in alphanumeric versus color/ object naming 2015 Archives of Clinical Neuropsychology USA Whipple, Nelson (7) To investigate the performance in adolescents and young adults with ADHD, Reading Disorder (RD), and ADHD/RD on measures of alphanumeric and nonalphanumeric naming speed and the relationship between naming speed and academic achievement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reading comprehension in boys with ADHD: the mediating roles of working memory and orthographic conversion (16) 61 boys aged 8 to 12 years: 31 with ADHD and 30 without ADHD or other psychological and mental disorders. CE (central executive), orthgraphic conversion and reading comprehension showed worse results in the ADHD group than in the control group, which influenced reading comprehension indirectly by means of the functioning of the CE on the orthographic system.…”
mentioning
confidence: 99%
“…In addition, a study of investigating the connection between working memory and reading outcomes conducted by Dahlin (2011) revealed that individual working memory was significantly correlated to young learners' reading achievements and the training effects of working memory were found to benefit L2 learners' development of reading comprehension. More recently, Friedman et al (2017) examined the contributing factors to reading comprehension disabilities in learners with Attention-Deficit Disorder. They demonstrated that IDs in working memory and orthographic conversion were the key elements relating to the difference of reading comprehension to ADD learners.…”
Section: Working Memory On Readingmentioning
confidence: 99%